Penerapan Kurikulum Merdeka di SMP: Kegiatan Intrakurikuler dan Ekstrakurikuler, Integrasi Muatan Lokal, dan Penguatan Pengalaman Pembelajaran (SLR) - Sitorus, Friska Ria; Roniati; Simangunsong, Yovita; Br Barus, Selviani (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
This research aims to conduct a comprehensive analysis of the implementation of the Independent Learning Curriculum in Junior High Schools (SMP) using a Systematic Literature Review (SLR) approach. This research uses the Systematic Literature Review (SLR) method to collect, evaluate and synthesize literature related to the implementation of the Independent Learning Curriculum in Middle Schools. The steps include developing a research protocol, searching for literature using certain keywords, selecting articles based on certain criteria, evaluating the quality of the articles, and analyzing data to formulate the 4 best article manuscripts with main findings and systematic implications of the results. The result of this work is the implementation of the Independent Learning Curriculum in various schools integrating intracurricular and extracurricular activities with a focus on developing local content, Informatics and Crafts skills, as well as flexible formative assessment. The combination of intracurricular and extracurricular activities allows students to develop holistic skills in accordance with an educational vision that is adaptive and relevant to future needs. The integration of local content in the curriculum creates a learning environment that inspires and supports students' comprehensive development. This curriculum emphasizes strengthening learning experiences by considering real aspects such as waste management and green entrepreneurship. Alignment between learning programs that focus on direct experience and the goals of the Independent Learning Curriculum produces a dynamic